Analysis of the relationship between anthropometric Characteristics and archery performance (Journal of Advances and Scholarly Researches in Allied Education, 2025)
Purpose: This study aims to analyze the relationship between anthropometric variables and archery performance in elite male recurve archers. Understanding these correlations can help optimize training strategies and talent identification in the sport of archery.Methods: A purposive sampling technique was used to select five Indian international-level male recurve archers from the SAI Archery Training Center, Sonipat. Anthropometric measurements including arm span, body mass index (BMI), fat mass, height, muscle mass (arms and legs), skeletal muscle mass, sitting height ratio, waist-hip ratio, and weight were recorded using standard procedures. Performance parameters such as anchor, draw, follow-through, reasoning, release, and T-stance were also assessed. Pearson’s correlation analysis was conducted to determine relationships between anthropometric variables and archery performance.Results: The findings revealed strong positive correlations between height and muscle mass distribution, emphasizing the role of body structure in athletic performance. Skeletal muscle mass showed a significant correlation with release efficiency (r = 0.816, p < 0.05), arm span positively correlated with release (r = 0.896, p < 0.05), indicating its importance in movement execution. Additionally, fat mass demonstrated negative correlations with key performance variables, suggesting that lean body composition is advantageous for precision in archery. The study also highlighted symmetry in muscle mass distribution, a crucial factor in achieving consistent shooting performance.Conclusion: The study concludes that anthropometric attributes, particularly arm span, skeletal muscle mass, and overall lean body composition, play a crucial role in archery performance. These findings emphasize the importance of targeted strength training and body composition management for optimizing performance in elite archers.